Comparative proteome analysis of the tegument of male and female adult Schistosoma mansoni - Winkelmann, Franziska; Gesell Salazar, Manuela; Hentschker, Christian; Michalik, Stephan; Macháček, Tomáš; Scharf, Christian; Reisinger, Emil C; Völker, Uwe; Sombetzki, Martina (Scientific reports, 2022)
The tegument, as the surface layer of adult male and female Schistosoma spp. represents the protective barrier of the worms to the hostile environment of the host bloodstream. Here we present the first comparative analysis of sex-specific tegument proteins of paired or virgin Schistosoma mansoni. We applied a new and highly sensitive workflow, allowing detection of even low abundance proteins. Therefore, a streptavidin-biotin affinity purification technique in combination with single pot solid-phase enhanced sample preparation was established for subsequent LC-MS/MS analysis. We were able to identify 1519 tegument proteins for male and female virgin and paired worms and categorized them by sex. Bioinformatic analysis revealed an involvement of female-specific tegument proteins in signaling pathways of cellular processes and antioxidant mechanisms. Male-specific proteins were found to be enriched in processes linked to phosphorylation and signal transduction. This suggests a task sharing between the sexes that might be necessary for survival in the host. Our datasets provide a basis for further studies to understand and ultimately decipher the strategies of the two worm sexes to evade the immune system.
Keywords: ženské pohlaví; Female; Schistosoma mansoni; Animals; proteiny červů; Male; tandemová hmotnostní spektrometrie; Tandem Mass Spectrometry; Proteome; mužské pohlaví; Chromatography, Liquid; chromatografie kapalinová; zvířata; proteom; Helminth Proteins